OROPHARYNGEAL DYSPHAGIA IN ELDERLY PERSONS - ETIOLOGY, PATHOPHYSIOLOGY AND SYMPTOMATOLOGY - Petrovic Lazic, Mirjana; Babac, Snezana; Ilic Savic, Ivana (Sanamed, 2022)
Swallowing disorders can occur at any age, although they occur more often in old age when the physiology of swallowing changes due to aging. Oropharyngeal dysphagia is a very common clinical condition affecting 13% of the total population over 65 years of age and 51% of institutionalized older people. Given that oropharyngeal dysphagia can lead to increased morbidity and mortality in the elderly, it is necessary to prevent the occurrence of dysphagia in this population group as much as possible. In relation to this, the paper aims to provide insight into contemporary research into the etiology, pathophysiology, and symptomatology of oropharyngeal dysphagia in the elderly. In this review study, the electronic databases of Google Scholar Advanced Search and the Consortium of Serbian Libraries for Unified Procurement - KoBSON were searched. The following keywords and phrases were used in the search: swallowing, dysphagia, oropharyngeal dysphagia, aging, age and dysphagia, etiology of oropharyngeal dysphagia, the clinical picture of oropharyngeal dysphagia, pathophysiology of oropharyngeal dysphagia. This systematic review and meta-analysis of papers showed significant progress in the effective diagnostic approach of oropharyngeal dysphagia during the last years but also a significant lack of knowledge about adequate modifications of drugs applied during the treatment of patients with dysphagia. A good understanding of the etiology, pathophysiology, and symptomatology of oropharyngeal dysphagia would eliminate the harmful effects of pharmacological substances on the function of swallowing, given that the elderly, on the advice of a doctor, use them daily.
Keywords: swallowing disorders; oropharyngeal dysphagia; aging